Diagnosis accuracy of ultrasonography for acute colonic diverticulitis: a diagnostic meta-analysis - Guo, Jingyi; Yan, Fuqiang; Huang, Shanshan; Lyu, Guorong (Abdominal radiology (New York), 2025)
This study aims to evaluate the diagnostic accuracy of ultrasonography for acute colonic diverticulitis (ACD) and its ability to differentiate between uncomplicated and complicated diverticulitis. A comprehensive literature search was conducted from database inception to November 2024. The Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) tool was used to appraise study quality. Statistical analyses, including pooled sensitivity, specificity, likelihood ratios, diagnostic odds ratio (using random-effects models), and summary receiver operating characteristic (ROC) curve, were performed using Stata 15.0. Sixteen studies involving 5,019 subjects were included. The pooled sensitivity and specificity of ultrasonography for diagnosing ACD were 0.92 and 0.97, respectively. The area under the ROC curve was 0.93. For distinguishing uncomplicated from complicated diverticulitis, the sensitivity was 0.93, but specificity was lower at 0.60. Ultrasonography demonstrated high diagnostic accuracy for ACD (AUC = 0.93), with pooled sensitivity of 0.92 and specificity of 0.97. While it was effective for initial diagnosis, its lower specificity (0.60) in distinguishing uncomplicated from complicated cases suggested it should be integrated with complementary diagnostic modalities to optimize accuracy and guide personalized management strategies.